PELAKSANAAN TUGAS KARYAWAN RESEPSIONIS DI HOTEL TRUNTUM KUTA FORMERLY GRAND INNA KUTA BALI - Sinaga, Gracella Agnes; ', Etika (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This study aims to analyze the implementation of the duties of receptionist employees at the Truntum Kuta Hotel, Bali, especially regarding quality, quantity, implementation of their duties and responsibilities in serving guests. Hotel Truntum Kuta, previously known as Grand Inna Kuta, is a four-star hotel with an international reputation in Bali. As the number of tourists increases, the demand for professional reception services also increases. This study uses a qualitative descriptive method to describe the objective conditions of employee performance through observation, interviews and documentation. Research subjects involved managers, supervisors and Front Office employees. The results of the research show that the receptionist's duties at the Truntum Kuta Hotel have met the established standards, however several obstacles, such as a lack of labor due to cost savings policies, affect service to guests. It is hoped that these findings will provide insight for management in improving the quality of receptionist services and forming a positive image of the hotel. Keywords: Implementation of Employee Duties, Receptionist, Hotel, Service, Hotel Truntum Kuta